2014
DOI: 10.1111/iej.12354
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm activity of three irrigation protocols activated by ultrasonic, diode laser or Er:YAG laser in vitro

Abstract: The use of NaOCl after or in combination with a chelator caused the greatest reduction of E. faecalis. Diode laser and Er:YAG laser activation were superior to ultrasonics in dentinal tubule disinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
158
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(166 citation statements)
references
References 50 publications
5
158
1
2
Order By: Relevance
“…The majority of the remaining bacteria may have been located in regions of the root canal system which are impervious to physical or chemical disruption by NaOCl when delivered via a syringe (9,29). A significant difference was not shown between UAI and LAI 0.5 W or between UAI and LAI 0.75 W. These findings are in agreement with the previous studies conducted by Peters Bardsley et al (2011) and Neelakantan Cheng et al (2014) who did not find a significant bacterial reduction between LAI and UAI for 6% NaOCl (10,28). Compared to the UAI and LAI 0.5W groups, SEM qualitative analysis showed that there were co-aggregated bacteria and small areas of biofilm remaining in the LAI 0.75 W group (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The majority of the remaining bacteria may have been located in regions of the root canal system which are impervious to physical or chemical disruption by NaOCl when delivered via a syringe (9,29). A significant difference was not shown between UAI and LAI 0.5 W or between UAI and LAI 0.75 W. These findings are in agreement with the previous studies conducted by Peters Bardsley et al (2011) and Neelakantan Cheng et al (2014) who did not find a significant bacterial reduction between LAI and UAI for 6% NaOCl (10,28). Compared to the UAI and LAI 0.5W groups, SEM qualitative analysis showed that there were co-aggregated bacteria and small areas of biofilm remaining in the LAI 0.75 W group (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Compared to the UAI and LAI 0.5W groups, SEM qualitative analysis showed that there were co-aggregated bacteria and small areas of biofilm remaining in the LAI 0.75 W group (Fig. A similar result was observed by Neelakantan et al (2014) who found that UAI and LAI to be equally effective at reducing bacteria number when 3% NaOCl and 17% EDTA were used in a NaOCl-EDTA-NaOCl combination with a total activation time of 4 min and a contact time of 6 min (28). This is a surprising result and may have occurred because LAI (0.75 W) fluid dynamics did not improve the flow of 4% NaOCl into the deeper recesses of the root canal system.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, by virtue of its effect on the smear layer, HEDP can enhance the disinfection efficacy of NaOCl in experimentally infected root canals (Neelakantan et al . ) and dentinal tubules (Morago et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…The most important reason for not using NiTi instruments seems to be lack of adequate education. [4] [14] Conclusion:-Dentists are familiar with limitations of NiTi instruments and techniques. Moreover, they are increasing efficacy of their practice by using these appliances.…”
Section: Discussion:-mentioning
confidence: 99%